PArticipants' Accounts (2008)
This article presents how some children have experienced EAFIT Children's University. Daniel Velásquez Rodríguez and Santiago are brothers; they participate in the hotbed of reseach for school students entitled Process Improvement. Michel Castañeda was part of the hotbed of Robotics. Sandra Cárdenas and her son Mateo come to EAFIT every month. She is a math teacher and he is in the third grade at the school where his mother works.